(3GdQjGVjGJ aj GdYdhe GdeGdjI hGdEOGQjIs - (3KGFQ ajUd(B, (3TGgQs; (3SGeQ eMeO YchQ(B, s ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2008)
(3eaGgje QjGVjI CSGSjI dHfGA GdfehPL GdQjGVj, eaghe GdOGdI hGdOGdI GdNWjI (B-(3GdefXheI GdNWjI hGdJhGRf aj GdShb, GdeYGOdGJ hGdOhGd GdJQHjYjI, GdeYGOdGJ hGdOhGd GdCSjI hGddhZGQjJejI hJWHjbGJgG GdEbJUGOjI, GdQjGVjGJ aj GdYdhe GdeGdjI, GdJaGVd hJWHjbGJg GdEbJUGOjI, GdJaGVd GdLRFj, GdeUahaGJ hJWHjbGJgG GdEbJUGOjIs
((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdGOGQIs; (3GdJaGVd hGdJcGeds; (3GdQjGVjGJs; (3GdeUahbGJs